Tradeoffs between the use of improved varieties and agrobiodiversity conservation in the Sahel - Kouakou, A.; Abdoulaye, T. (2025)
The issue of sustainable agrifood systems, especially the existence of possible tradeoffs between agricultural intensification (through the use of improved varieties) and agrobiodiversity conservation is of high policy relevance in Sub-Saharan Africa. We measure spatial varietal diversity and examine the effects of growing improved varieties of pearl millet and groundnut on varietal diversity on farms in Mali and Niger. We find that the diffusion of improved pearl millet varieties contributes to fewer varieties grown in Niger, whereas it contributes to more varieties grown in Mali. In the case of groundnut, the diffusion of improved varieties does not displace the other varieties grown in Mali and Niger. We conclude that in the case of pearl millet in Niger, it is important to ensure that the number and type of improved varieties released be widened to avoid loss of agrobiodiversity. For groundnut, the diffusion of improved varieties is not harming agrobiodiversity.